Cough: Contemporary Challenges. (2nd September 2014) - Stachler, Robert J.; Bock, Jonathan M.; Cohen, Seth M.; Altman, Kenneth W.
Abstract : Program Description: The purpose of this miniseminar is to present the contemporary management of cough. This miniseminar will thoroughly cover the most common etiologies of cough and its current management. A description of the sensory receptors, hyperexcitability related to neuropathy (including postviral), pharmacologic suppression of hyperexcitability, and management of pertussis (whooping cough) will be presented. If time allows, a few difficult cases will be presented that highlight the current management strategies. Educational Objectives: (1) Explain the multiple etiologies for cough and its management. (2) Examine the complex relationship between the cough receptors and the larynx. (3) Illustrate pertussis resurgence and contemporary management.